The effects of PM2.5 air pollution on human health: A narrative review with a focus on cerebrovascular diseases - Leticia Simo (Environmental Disease)
Ambient air pollution, particularly fine particulate matter (PM2.5), has emerged as a critical environmental determinant of human health. PM2.5 exerts its deleterious effects through complex pathways involving systemic inflammation, oxidative stress, endothelial dysfunction, and neurovascular damage, heightening the risks of ischemic stroke, hemorrhagic stroke, vascular cognitive impairment, and other cerebrovascular disorders. This paper synthesizes recent findings from epidemiological studies, mechanistic insights from experimental research, and global health data to elucidate the multifaceted impact of PM2.5 exposure on cerebrovascular health. It underscores the urgent need for integrated public health strategies aimed at mitigating air pollution’s impact on cerebrovascular diseases and safeguarding vulnerable populations.